A pre-lithiation silicon-oxygen composite material and its preparation method, negative electrode sheet, battery and application

By using prelithiated silicon oxygen composite materials with gradient distribution silicon microcrystals and stearate coatings in lithium-ion batteries, the low energy density and safety hazards of graphite negative electrode materials in lithium-ion batteries are solved, and the problem of low energy density and safety hazards of graphite negative electrode materials in lithium-ion batteries is achieved. High capacity, high first-time Coulomb efficiency and good cycle stability.

CN115148994BActive Publication Date: 2024-12-27NINGBO SHANSHAN NEW MATERIAL TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202210764990.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-29
Publication Date
2024-12-27
Estimated Expiration
2042-06-29

AI Technical Summary

Technical Problem

The low energy density and safety hazards of graphite negative electrode materials in existing lithium-ion batteries make it impossible to be suitable for power batteries. The prelithiated silicon oxygen negative electrode materials have too many residual lithium salts on the surface and are prone to side reactions on the material interface. The problem.

Method used

The prelithiated silicon oxygen composite material including amorphous silicon oxide, silicon microcrystals and lithium silicate as cores, carbon layer and stearate as coatings are used, and the carbon coating is used to coat them. The stearate surface is coated to form a gradient-distributed silicon microcrystals and conductive layer, which suppresses the volume expansion stress during lithium ion embedding and reduces the increase in irreversible capacity.

Benefits of technology

Effectively reduce residual lithium on the surface of the material, inhibit side reactions during charging and discharging, improve the capacity, first-time Coulomb efficiency and cycling stability of lithium-ion batteries, and enhance electrochemical performance and interface stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115148994B_ABST
    Figure CN115148994B_ABST
Patent Text Reader

Abstract

The present invention discloses a pre-lithiation silicon-oxygen composite material and a preparation method thereof, a negative electrode plate, a battery and an application thereof. The pre-lithiation silicon-oxygen composite material includes, from the inside to the outside, a core, a first coating layer and a second coating layer; the core includes amorphous silicon oxide, silicon microcrystals and lithium silicate; the first coating layer is a carbon layer; and the second coating layer is a stearate layer. The pre-lithiation silicon-oxygen composite material of the present invention can effectively reduce the residual lithium on the surface of the material, inhibit the side reactions of the material during the charge and discharge process, and enable the lithium-ion battery to have a high capacity, a high first coulomb efficiency and good charge and discharge cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a pre-lithiation silicon-oxygen composite material, a preparation method thereof, a negative electrode plate, a battery and applications thereof. Background Art

[0002] With the intensification of the fossil fuel crisis and the global greenhouse effect, the development of new energy has become an urgent task. The development of new energy must rely on advanced energy storage technology, among which lithium-ion batteries have become the focus of attention due to their high energy density, long cycle life and high average output voltage. Especially nowadays, the accelerated replacement of consumer electronic products, the vigorous development of the power vehicle industry, the rapid promotion of smart grids and the expansion of demand in other technical fields have further promoted the rapid development of the lithium-ion battery industry.

[0003] At present, commercial lithium-ion batteries use graphite as the negative electrode material. However, the two fatal defects of graphite negative electrodes: low energy density, low lithium specific capacity (372mAh / g) and safety hazards ("lithium precipitation" phenomenon) make them unsuitable for power batteries. Therefore, finding a new type of high-capacity, safe and long-cycle material to replace graphite negative electrode materials has become the key to the further development of power lithium-ion batteries. Silicon oxide negative electrode material.

[0004] Silicon oxide negative electrode materials have a high theoretical specific capacity, which theoretically brings 10 times the storage capacity of traditional graphite materials in lithium-ion batteries, and also has extremely high charging efficiency. However, the first coulombic efficiency of silicon oxide negative electrode materials is low (about 70%). Pre-lithiation is an effective method to improve the first efficiency of silicon oxide negative electrode materials. Chemical pre-lithiation is a common method for pre-embedding lithium into silicon oxide negative electrodes. However, there are many problems with pre-lithiation silicon oxide negative electrode materials, such as excessive residual lithium salts on the surface and side reactions that are prone to occur at the material interface. Summary of the invention

[0005] In order to overcome the defects of the prior art that the silicon-oxygen negative electrode material after pre-lithiation has too much residual lithium salt on the surface and the material interface is prone to side reactions, the present invention provides a pre-lithiation silicon-oxygen composite material and its preparation method, negative electrode plate, battery and application. The pre-lithiation silicon-oxygen composite material prepared by the present invention can effectively reduce the residual lithium on the surface of the material, inhibit the side reactions of the material during the charge and discharge process, and make the lithium-ion battery have high capacity, high initial coulomb efficiency and good charge and discharge cycle stability.

[0006] The present invention provides a pre-lithiation silicon-oxygen composite material, which comprises a core, a first coating layer and a second coating layer from the inside to the outside; the core comprises amorphous silicon oxide, silicon microcrystals and lithium silicate; the first coating layer is a carbon layer; and the second coating layer is a stearate layer.

[0007] In the present invention, the diameter of the inner core may be 1 to 20 μm.

[0008] In the present invention, the thickness of the first coating layer may be 1 to 100 nm.

[0009] In the present invention, the thickness of the second coating layer may be 1 to 100 nm.

[0010] In the present invention, the chemical formula of the amorphous silicon oxide may be SiO x , 0 <x≤2。

[0011] In the present invention, the grain size of the silicon microcrystals may be 1 to 10 nm.

[0012] The grain size of the silicon microcrystals increases in a gradient from the center of the core to the surface of the core. That is, the grain size of the silicon microcrystals at the center of the core is the smallest, and the grain size of the silicon microcrystals at the surface of the core is the largest. The silicon microcrystals with gradually varying sizes are distributed in the amorphous silicon oxide main material, which can guide the huge volume expansion stress generated during the lithium insertion process to be released outward, thereby inhibiting the volume expansion of the silicon-based negative electrode material, reducing the irreversible capacity increase caused by this, and effectively improving the cycle life of the silicon-based negative electrode material.

[0013] In the present invention, the second coating layer comprises at least one of magnesium stearate, calcium stearate or zinc stearate.

[0014] In the present invention, the mass of the first coating layer accounts for 4.5-8.5% of the total mass of the core and the first coating layer.

[0015] In the present invention, the mass of the second coating layer may account for 0.1-5% of the total mass of the pre-lithiation silicon-oxygen composite material.

[0016] In the present invention, the specific surface area of ​​the pre-lithiation silicon-oxygen composite material can be 1 to 10 m 2 / g.

[0017] The silicon source and the lithium source are mixed and calcined to obtain the core, which is then mixed with the carbon source and annealed again to obtain the pre-lithiated silicon-oxygen material with a carbon layer, and finally the surface is coated with stearate (abbreviated as MS) to obtain

[0018] The present invention also provides a method for preparing a pre-lithiation silicon-oxygen composite material, which comprises the following steps:

[0019] S1, performing carbon coating treatment on the inner core to obtain a carbon coated inner core;

[0020] S2, drying the mixture of the carbon-coated core, stearate and organic solvent;

[0021] The applicant found that after the inner core is treated with carbon coating, it is mixed with stearate and organic solvent, and after appropriate coating modification, stearate is formed in the outermost layer. Further testing found that the pre-lithiation silicon-oxygen composite material obtained by this preparation method exhibits better electrochemical performance.

[0022] In S1 of the present invention, the thickness of the carbon coating layer of the carbon-coated core can be adjusted by the amount of carbon source used.

[0023] In S1 of the present invention, the core includes amorphous silicon oxide, silicon microcrystals and lithium silicate.

[0024] In step S2 of the present invention, the mass ratio of the stearate to the carbon-coated core may be 0.1 to 5:100, preferably 1 to 3:100, for example 2:100.

[0025] In step S2 of the present invention, the stearate may be at least one of magnesium stearate, calcium stearate and zinc stearate.

[0026] In step S2 of the present invention, the organic solvent may be a solvent commonly used in the art, generally one or more of anhydrous ethanol, anhydrous methanol, n-propanol, isopropanol, n-butanol and acetone.

[0027] In the present invention S1, the diameter of the inner core is determined by the size of the initial raw material, preferably 1 to 20 μm. In the present invention S1, the preparation method of the inner core can be a conventional preparation method in the art.

[0028] In S1 of the present invention, the core can be prepared by conventional methods in the art, generally by calcining a silicon source and a lithium source in an inert atmosphere.

[0029] Wherein, the silicon source may be silicon monoxide and / or silicon dioxide.

[0030] The lithium source may be an inorganic lithium compound or metallic lithium, preferably one or more of lithium hydroxide, lithium acetate, lithium carbonate, lithium hydride, and lithium aluminum hydride.

[0031] The molar ratio of the silicon source to the lithium source can be conventional in the art, as long as the lithium source can be completely converted into the LSO, and can generally be (1-20):1, such as 1:1.2 or 1:1.5.

[0032] The calcination temperature may be 400-800°C, for example, 500°C, 600°C or 700°C.

[0033] The calcination time may be sufficient for the lithium source and the silicon source to react completely, generally 1 to 10 hours, such as 2 hours or 6 hours.

[0034] In the present invention, the LSO is a lithium silicate containing Li2SiO3.

[0035] In step S1 of the present invention, the carbon coating treatment method can adopt a conventional solid phase carbon coating method in the art, which can generally be obtained by mixing the core with a carbon source under an inert atmosphere and calcining.

[0036] The carbon source may be an organic carbon source, preferably one or more of petroleum-based asphalt, glucose, sucrose, polyethylene glycol, and polyvinyl alcohol.

[0037] The calcination temperature may be 700-1000°C, for example 800°C.

[0038] Wherein, the calcination time can be 4 hours.

[0039] In step S2 of the present invention, the mixture can be prepared by stirring the carbon-coated core, stearate and an organic solvent.

[0040] Wherein, the stirring temperature may be room temperature.

[0041] The stirring time may be 20 to 40 minutes, for example 30 minutes.

[0042] In step S2 of the present invention, the drying temperature may be 60-80°C.

[0043] In step S2 of the present invention, the drying time may be 12 to 24 hours.

[0044] The present invention also provides a pre-lithiation silicon-oxygen composite material, which is prepared by the above-mentioned preparation method.

[0045] The present invention also provides an application of the pre-lithiation silicon-oxygen composite material in electrode materials.

[0046] The present invention also provides a negative electrode plate, which is made of the above-mentioned pre-lithiation silicon-oxygen composite material. The preparation steps include: homogenizing a mixture of the pre-lithiation silicon-oxygen composite material, a binder and a conductive agent, coating it on a copper foil, vacuum drying it, and rolling it to obtain a negative electrode plate.

[0047] Wherein, the mass ratio of the pre-lithiation silicon-oxygen composite material, the binder and the conductive agent may be 70:20:10.

[0048] Wherein, the conductive agent is preferably Super P; the binder is preferably LA132 (10wt%); and the dispersant is preferably deionized water.

[0049] The present invention also provides a lithium-ion battery, which comprises the above-mentioned negative electrode plate.

[0050] The preparation method of the lithium ion battery may include the following steps: 1 mol / L LiPF6 mixed solvent is used as an electrolyte, the mixed solvent is a mixture of ethyl carbonate: dimethyl carbonate: ethyl methyl carbonate = 1:1:1 in volume ratio, a polypropylene microporous membrane is used as a diaphragm, a metal lithium sheet is used as a counter electrode, and the above-mentioned electrode made of the pre-lithiated silicon-oxygen composite material coated with stearate is assembled into a button battery in an inert gas glove box system filled with argon.

[0051] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0052] The reagents and raw materials used in the present invention are commercially available.

[0053] The positive and progressive effects of the present invention are:

[0054] The invention prepares a pre-lithiation silicon-oxygen composite material by subjecting the inner core to carbon coating treatment, then mixing with stearate and an organic solvent and drying, wherein the stearate forms a coating layer on the surface of the carbon-coated inner core.

[0055] When the pre-lithiation silicon-oxygen composite material prepared by the present invention is used in the electrode of a lithium-ion battery, the obtained lithium-ion battery has high capacity, high initial charge and discharge efficiency, and good cycle performance; at the same time, the pre-lithiation silicon-oxygen composite material has good water resistance, so that less gas is produced during the process of manufacturing it into a pole piece, and the slurry has good stability; and the interface stability with the electrolyte is improved, thereby improving the electrochemical performance of the negative electrode. At the same time, the method has simple process, low cost, wide application range, is conducive to industrial production, and has the prospect of further promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 Schematic diagram of the structure of the silicon-oxygen negative electrode material provided in Example 1 of the present application. (1-core, 2-first coating layer, 3-second coating layer) DETAILED DESCRIPTION

[0057] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0058] The structure of the pre-lithiated silicon-oxygen composite material is expressed as Si / SiOx / LSO@C@MS. Here, "@" refers to the core-shell structure, where LSO contains Li2SiO3; MS refers to magnesium stearate; Si / SiOx / LSO@C refers to the carbon-coated core; Si / SiOx / LSO@C@MS refers to a pre-lithiated silicon-oxygen composite material with SiOx / LSO as the core and carbon layer and magnesium stearate as the shell.

[0059] Example 1

[0060] (1) Silicon dioxide and lithium hydride are uniformly mixed in a molar ratio of 1:1.2, then put into a graphite crucible, placed in a box furnace and calcined at 500° C. for 4 h under an argon atmosphere, and then cooled to obtain Si / SiOx / LSO;

[0061] (2) placing the pre-lithiated silicon oxide core and polyvinyl alcohol in a mass ratio of 100:0.5 in a tube furnace, heating to 700 °C under an argon atmosphere, and calcining for 4 h to obtain Si / SiOx / LSO@C;

[0062] (3) Magnesium stearate and carbon-coated pre-lithiated silicon-oxygen material were placed in anhydrous ethanol at a mass ratio of 1:100, stirred for 20 minutes, and then placed in a vacuum drying oven at 80°C for 24 hours to obtain Si / SiOx / LSO@C@MS.

[0063] Example 2

[0064] The specific process is the same as in Example 1, except that the calcination temperature in step (2) is adjusted to 600°C.

[0065] Example 3

[0066] The specific process is the same as in Example 1, except that the calcination temperature in step (2) is adjusted to 800°C.

[0067] Example 4

[0068] The specific process is the same as in Example 1, except that the mass ratio of magnesium stearate to carbon-coated pre-lithiated silicon oxide material in step (3) is adjusted to 0.5:100.

[0069] Example 5

[0070] The specific process is the same as in Example 1, except that the mass ratio of magnesium stearate to carbon-coated pre-lithiated silicon oxide material in step (3) is adjusted to 2:100.

[0071] Comparative Example 1

[0072] The specific process is the same as in Example 1, except that there is no step (3).

[0073] Comparative Example 2

[0074] The specific process is the same as in Example 1, except that the magnesium stearate in step (3) is replaced by polyoxyethylene.

[0075] Effect Example 1

[0076] 1. Determination of electrochemical properties

[0077] The pre-lithiation silicon-oxygen composite material coated with stearate prepared in each embodiment and comparative example is coated on copper foil, and vacuum dried and rolled to prepare a negative electrode sheet; a 1 mol / L LiPF6 three-component mixed solvent is used, and the electrolyte is mixed in a volume ratio of ethyl carbonate: dimethyl carbonate: ethyl methyl carbonate = 1:1:1, a polypropylene microporous membrane is used as a diaphragm, and a metal lithium sheet is used as a positive electrode. It is assembled into a button battery in an inert gas glove box system filled with argon. The charge and discharge test of the button battery was carried out on the LAND battery testing system of Wuhan Jinnuo Electronics Co., Ltd., at room temperature, 0.1C constant current charge and discharge, and the charge and discharge voltage was limited to 0.005~1.5V. The cycle stability is the ratio of its specific capacity to the initial specific capacity after 50 charge and discharge cycles under the same test conditions. The lower the value, the faster the capacity decreases and the worse the cycle stability. The charge and discharge data are shown in Table 1.

[0078] 2. Gas production test method

[0079] Pipette 5 mL of the prepared slurry into a sealed syringe, mark the movable piston, and observe the piston movement distance after 24 hours.

[0080] Table 1

[0081]

[0082] From the above experimental results, it can be seen that the magnesium stearate coating prepared by the method of the present invention can form a stable interface and maintain relatively stable electrochemical performance. At the same time, it was found in the slurry preparation process that the modified pre-lithiation silicon oxygen negative electrode material has good slurry stability and does not precipitate during the slurry preparation process.

[0083] (1) The structural schematic diagram of Si / SiOx / LSO@C@MS prepared in Example 1 of the present invention is as follows Figure 1 As shown. The first-week capacity of the lithium-ion battery applied to it can reach 1406.9mAh / g, and the capacity after modification is higher and the first efficiency is higher; the carbon coating temperatures of Examples 2 and 3 are 600°C and 800°C, respectively, and they also have good effects. Compared with the materials obtained by coating at 700°C, the effect is poor, indicating that in the process of carbon coating, the heat treatment temperature is too low and the carbon coating layer may not be completely carbonized, and the conductivity is low. If the temperature is too high, the conductivity of the carbon layer will also decrease, affecting the electrochemical performance and resulting in reduced capacity; Examples 4 and 5 are to adjust the coating amount of magnesium stearate. When within the scope of the present invention, the obtained material has a good effect. It has been found that when the amount of coating is too small, the coating effect is not ideal; when the coating amount is too much, the slurry is stable and does not produce gas, but the coating layer is too thick and the coating layer has poor conductivity, which leads to a decrease in the capacity of the electrode material during the first charge and discharge process and a decrease in the first coulomb efficiency.

[0084] (2) Comparative Examples 1 and 2 show that the products without magnesium stearate coating have lower reversible capacity and lower initial efficiency of the battery, and the stabilization effect of the slurry is poor during the preparation of the slurry, and the gas generation is serious.

[0085] The above is a description of the specific embodiments of the present invention. It should be noted that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which will not affect the essence of the present invention.

Claims

1. A pre-lithiation silicon-oxygen composite material, characterized in that: It includes a core, a first coating layer and a second coating layer from the inside to the outside; the core includes amorphous silicon oxide, silicon microcrystals and lithium silicate; the first coating layer is a carbon layer; the second coating layer is a stearate layer; The preparation method of the pre-lithiation silicon-oxygen composite material comprises the following steps: S1, performing carbon coating treatment on the inner core to obtain a carbon coated inner core; S2, drying the mixture of the carbon-coated core, stearate and organic solvent to obtain; In step S1, the carbon coating method adopts a solid phase carbon coating method; the carbon coating method is to mix the inner core with a carbon source under an inert atmosphere and calcine to obtain the inner core; the carbon source is one or more of petroleum-based asphalt, glucose, sucrose, polyethylene glycol, and polyvinyl alcohol.

2. The pre-lithiation silicon-oxygen composite material according to claim 1, characterized in that: The diameter of the core is 1-20 μm; And / or, the thickness of the first coating layer is 1-100 nm; And / or, the thickness of the second coating layer is 1-100 nm; And / or, the chemical formula of the amorphous silicon oxide is SiO x , 0 <x≤2; And / or, the grain size of the silicon microcrystals is 1-10 nm; And / or, the grain size of the silicon microcrystals increases in a gradient along the direction from the center of the core to the surface of the core; And / or, the second coating layer comprises at least one of magnesium stearate, calcium stearate and zinc stearate; and / or, the mass of the first coating layer accounts for 4.5-8.5% of the total mass of the core and the first coating layer; And / or, the mass of the second coating layer accounts for 0.1-5% of the total mass of the pre-lithiation silicon-oxygen composite material.

3. The pre-lithiation silicon-oxygen composite material according to claim 1, characterized in that: The mass ratio of the stearate to the carbon-coated core is 0.1 to 5:100; And / or, the stearate is at least one of magnesium stearate, calcium stearate and zinc stearate; and / or, the organic solvent is one or more of anhydrous ethanol, anhydrous methanol, n-propanol, isopropanol, n-butanol and acetone; And / or, the inner core is prepared by calcining a silicon source and a lithium source in an inert atmosphere.

4. The pre-lithiated silicon-oxygen composite material according to claim 3, characterized in that: The mass ratio of the stearate to the carbon-coated core is 1-3:

100.

5. The pre-lithiation silicon-oxygen composite material according to claim 4, characterized in that: The mass ratio of the stearate to the carbon-coated core is 2:

100.

6. The pre-lithiation silicon-oxygen composite material according to claim 3, characterized in that: The silicon source is silicon dioxide and / or silicon monoxide; And / or, the lithium source is an inorganic lithium compound or metallic lithium; And / or, the molar ratio of the silicon source to the lithium source is 1:1.2 or 1:1.5; And / or, the calcination temperature is 400-800°C; And / or, the calcination time is 1 to 10 hours; And / or, the calcination temperature is 700-1000°C; And / or, the calcination time is 4 hours.

7. The pre-lithiated silicon-oxygen composite material according to claim 6, characterized in that: The lithium source is one or more of lithium hydroxide, lithium acetate, lithium carbonate, lithium hydride, and lithium aluminum hydride; And / or, the calcination temperature is 500° C., 600° C. or 700° C.; And / or, the calcination time is 2h or 6h; And / or, the calcination temperature is 800°C.

8. The pre-lithiated silicon-oxygen composite material according to claim 1, wherein: The mixture is prepared by stirring the carbon-coated core, stearate and organic solvent; wherein the stirring temperature is 20-30° C.; wherein the stirring time is 20-40 min; And / or, the drying temperature is 60-80°C; And / or, the drying time is 12 to 24 hours.

9. The pre-lithiated silicon-oxygen composite material according to claim 8, characterized in that: The stirring time is 30 min.

10. Use of the pre-lithiated silicon-oxygen composite material according to any one of claims 1 to 9 in electrode materials.

11. A negative electrode plate, characterized in that: It is prepared using the pre-lithiation silicon-oxygen composite material as described in any one of claims 1 to 9.

12. A lithium ion battery, characterized in that: It includes the negative electrode sheet as claimed in claim 11.

Citation Information

Patent Citations

  • Lithium ion battery grade silicon monoxide negative electrode material and preparation method and application thereof

    CN111900368A

  • Carbon-coated silicon-based negative electrode material and preparation method thereof

    CN112164779A

  • Modified pre-lithiated silica material, and preparation method thereof, application and lithium ion battery

    CN112820863A

  • Modified pre-lithiated silica composite material as well as preparation method and application thereof

    CN113948688A

  • Modified pre-lithiated silica material, preparation method and application thereof and lithium ion battery

    CN114597341A